2022
DOI: 10.1177/00420980221079462
|View full text |Cite
|
Sign up to set email alerts
|

Social pathologies and urban pathogenicity: Moving towards better pandemic futures

Abstract: In this article, we suggest rethinking how to move forward in a way that better elucidates socio-economic and political factors driving inequities, and in turn points to more broad sweeping, deep-rooted changes necessary if pandemics in the future are finally going to be mitigated pre-emptively rather than reactively. To this end, we argue that a more comprehensive, flexible and incisive approach is necessary – a hermeneutic framework that focuses analytical attention and action on interventions upstream, on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…A prime illustration of this phenomenon was observed during the transformation of Vibrio cholerae from non-pathogenic to pathogenic variants, the process of which entails the acquisition of the type IV toxinco-regulated pilus (TCP) followed by infection with the filamentous phage CTXϕ, exploiting pilus as an entry point and introducing genes coding the production of cholera toxin. Current studies strongly indicate that specific distributed genes and gene combinations play crucial roles in determining which kinds of strains are most likely to act as pathogens [73][74][75]. The most prevalent pathogen genes included RpoB (belonging to Acinetobacter baumannii), followed by RSc0454 and speC (Ralstonia solanacearum), as well as CcoN2 and rmlA (Pseudomonas aeruginosa).…”
Section: (4) Corynebacteriaceae Familymentioning
confidence: 99%
“…A prime illustration of this phenomenon was observed during the transformation of Vibrio cholerae from non-pathogenic to pathogenic variants, the process of which entails the acquisition of the type IV toxinco-regulated pilus (TCP) followed by infection with the filamentous phage CTXϕ, exploiting pilus as an entry point and introducing genes coding the production of cholera toxin. Current studies strongly indicate that specific distributed genes and gene combinations play crucial roles in determining which kinds of strains are most likely to act as pathogens [73][74][75]. The most prevalent pathogen genes included RpoB (belonging to Acinetobacter baumannii), followed by RSc0454 and speC (Ralstonia solanacearum), as well as CcoN2 and rmlA (Pseudomonas aeruginosa).…”
Section: (4) Corynebacteriaceae Familymentioning
confidence: 99%
“…Building upon the extensive research on pandemics and social inequalities, Atuk and Craddock (2023) propose an innovative 'pathogenicity' framework to rethink how cities can be better prepared for future public health emergencies. The 'pathogenicity' framework, originally proposed by Hinchliffe et al (2016) in the context of global biosecurity, reconceptualises disease as a situated matter: that is to say, disease is not a fixed object but a process of various conditions being formed which allow for disease emergence and transmission.…”
Section: Urban Governance and Civil Societymentioning
confidence: 99%
“…The ‘pathogenicity’ framework, originally proposed by Hinchliffe et al (2016) in the context of global biosecurity, reconceptualises disease as a situated matter: that is to say, disease is not a fixed object but a process of various conditions being formed which allow for disease emergence and transmission. By translating Hinchliffe et al’s (2016) ‘pathogenicity’ framework to urban settings, Atuk and Craddock (2023) make a compelling argument that making communities healthier at all times would have greater effectiveness in managing pandemics than episodic public health preparedness in times of crises. As Atuk and Craddock (2023: 1670) write, COVID-19…has shown that the neoliberal tendency to address harm only when there are crises and disasters, and to divest from programmes that might eradicate some of the root causes of unequal burdens of disease such as reduction of public investment, privatisation of healthcare and impoverishment of public health infrastructures…becomes quite literally murderous to millions.…”
Section: Urban Governance and Civil Societymentioning
confidence: 99%
See 2 more Smart Citations